The cost of delivering COVID-19 vaccines in Mozambique: a bottom-up costing study - Tozé Namalela; Flavia Moi; Amélia Dipuve; Pedro Marizane Pota; José Guambe; Maria Tereza Couto; Laura Boonstoppel (BMC Health Services Research)
Abstract Background Vaccines were a key tool in controlling the COVID-19 pandemic. However, the cost of delivering these vaccines in low- and middle-income countries was highly uncertain, due to the unprecedented delivery volume and the need to reach new target populations. To fill this evidence gap, this study estimates the cost of delivering COVID-19 vaccines in Mozambique. Methods This retrospective, bottom-up costing study estimated the financial and economic costs of delivering COVID-19 vaccines in 2022 USD, during the first year of introduction. Recurrent costs were collected for the initial rollout period (March 8th to April 8th 2021) and for a later, higher-volume period (December 1st 2021 to February 28th 2022). The study was conducted from a payer perspective. Data was collected at health facilities from a purposively selected sample of 27 vaccination sites, as well as from 6 district and provincial health offices in 2 provinces, the Ministry of Health, and development partners. The overall cost per dose was obtained by estimating and aggregating the volume-weighted average cost per dose for each administrative level. Qualitative interviews were also conducted to contextualize cost findings. Results The cost per dose for the first year of implementation was $1.14 for economic costs and $0.50 for financial costs. For the initial rollout period, when the volume delivered was low (64 doses/vaccination day on average), the economic cost per dose was $3.56 and decreased considerably to $0.85 when the program delivered at scale and volume delivered increased to 225 doses/vaccination day. Opportunity costs made up a considerable share of the economic cost per dose, 73% and 49% respectively during the initial rollout and when the program delivered at scale. The qualitative interviews found that political prioritization and workers’ commitment made the program possible despite little financial investment. Conclusions The cost of delivering COVID-19 vaccines in Mozambique was found to be low compared to other countries, due to heavy reliance on existing resources and little additional investment into the program. Findings from this study can support the government in planning and budgeting for the future of the COVID-19 vaccination program as well as other vaccination efforts.